What do health authorities think of population based health outcome indicators?. Issue 2 (June 1998) - McColl, A; Roderick, P; Gabbay, J; Ferris, G
Abstract : OBJECTIVES: To determine the role of population based indicators of health outcome in local health outcome assessments; the constraints of using such indicators; how they could be made more useful; and whether health authorities had developed their own indicators of health outcome. DESIGN: A structured telephone interview with representatives of 91 of the 100 English health authorities. RESULTS: Interviewees, asked to give details on two clinical areas in which population health outcome assessments had been of most value, nominated 147 examples in over 30 clinical areas. They chose 50 (34%) of the examples because of an outlying national indicator, and 20 (14%) because of local variations in a national indicator. The main perceived constraints in the use of population based indicators of health outcome were: data validity and timeliness; the attributability of these health outcomes to the quality of health care; the difficulties of changing clinical behavior; and organisational change within health authorities. To make these indicators more useful interviewees wanted an increased use of process indicators as proxies for health outcome, indicator trend data, and indicator comparisons of districts with similar population structures. Some recent publications have started to consider some of these issues. 27 (30%) health authorities had developed their own indicators, mostly provider based process indicators. 10 of these used their own indicators to manage the performance of local provider units. CONCLUSIONS: Population based indicators of health outcome had an important role in prompting districts to undertake population health outcome assessments. Health authorities also used these indicators to examine local variations in health outcome. They helped to highlight areas for further investigation, initiated data validation, and enabled the monitoring of changes to services. Comparative population based indicators of health outcome may have an increasing part to play in assessing the performance of health authorities.